Pentingnya Peran Lingkungan dalam Perkembangan Sosioemosional pada Anak Usia Middle Childhood - Purba, Julia; Sharon, Sofia Ruth; Al Faza, Rajendra Ahmad Dhafin; Putri, Raissa Dwifandra (Flourishing Journal, 2024)
The socio-emotional development of children in middle childhood is a crucial stage influenced by family, school, and peer environments. During this period, children begin to show significant improvements in social and emotional abilities and start to understand more complex social concepts such as friendship, conflict, and cooperation. This study aims to explore how various environmental aspects affect the socio-emotional maturity of children during this stage. Through a literature review of various research sources from the past ten years (2014-2024), it was found that secure attachment with parents, especially fathers, plays a significant role in the development of a child's self-esteem. A positive school environment and good relationships between students and teachers support better self-regulation and self-concept, while conflicts with teachers can disrupt a child's self-regulation. Reciprocal friendships among peers contribute to increased self-esteem and empathy. A supportive home environment and positive parenting also play a role in the consistent development of empathy. The conclusion of this study underscores the importance of positive relationships and consistent support from parents, teachers, and peers in shaping the socio-emotional development of children during middle childhood. AbstrakPerkembangan sosioemosional anak usia kanak-kanak menengah merupakan tahap penting yang dipengaruhi oleh lingkungan keluarga, sekolah, dan teman sebaya. Pada tahap ini, anak-anak mulai menunjukkan peningkatan signifikan dalam kemampuan sosial dan emosional, serta mulai memahami konsep sosial yang lebih kompleks seperti persahabatan, konflik, dan kerjasama. Penelitian ini bertujuan untuk mengeksplorasi bagaimana berbagai aspek lingkungan mempengaruhi kematangan sosio emosional anak pada periode ini. Melalui tinjauan literatur dari berbagai sumber penelitian dalam sepuluh tahun terakhir (2014-2024), ditemukan bahwa keterikatan yang aman dengan orang tua, terutama ayah, berperan besar dalam perkembangan self-esteem anak. Lingkungan sekolah yang positif dan hubungan yang baik antara siswa dan guru mendukung regulasi diri dan konsep diri yang lebih baik, sementara konflik dengan guru dapat mengganggu regulasi diri anak. Teman sebaya yang memiliki hubungan persahabatan timbal balik berkontribusi pada peningkatan self-esteem dan empati. Lingkungan rumah yang mendukung dan pengasuhan positif juga berperan dalam perkembangan empati yang konsisten. Kesimpulan dari penelitian ini menegaskan pentingnya hubungan yang positif dan dukungan konsisten dari orang tua, guru, dan teman sebaya dalam membentuk perkembangan sosioemosional anak pada masa kanak-kanak menengah.